DO PERSONAL VALUES INFLUENCE ORGANIZATIONAL COMMITMENT? - Sarah Silva Aguilar; André Luiz Mendes Athayde (Caderno de Administração)
The objective of the present study was to statistically test the influence of employees’ personal values ​​on their organizational commitment in a Brazilian public university. We adopted the Portuguese version of the Portrait Values ​​Questionnaire – Refined (SCHWARTZ et al., 2012) to measure personal values and the Portuguese version of the Managerial Decisions Questionnaire – Global (PETERSON; BARRETO; SMITH, 2016) to measure organizational commitment. The sample consisted of 220 employees, including administrative staff and faculty. We performed statistical analyzes with the IBM® SPSS® 20.0 software (Statistical Package for the Social Sciences). Spearman correlation tests (ρ) and multiple linear regressions (stepwise) explored how much of the employees’ organizational commitment variability could be explained by their personal values. The results showed statistically significant positive correlations between Conservation and organizational commitment and between Self-transcendence and organizational commitment. We also identified statistically significant negative correlations between Self-enhancement and organizational commitment. Deepening the results, we found that the personal values ​​of Self-transcendence and Self-enhancement can predict part of the variability of organizational commitment, the first positively and the second negatively. The study concludes that personal values may be a relevant variable in the study of organizational commitment.